POOLED MAPPING OF QUANTITATIVETRAIT LOCI ASSOCIATED WITH DROUGHT TOLERANCE IN RICE (ORYZA SATIVA L.) AT SEEDLING STAGE - Yingbao Wu; Gaoyang Zhang; Chao Zhang; Weiqi Tang; Ting Wang; Huining Zhang; Hongkai Wu (Journal of Animal and Plant Sciences, 2023)
Drought is among the foremost constraints influencing global rice productivity. The drought tolerance nature of rice is complicated, depending on multiple components and having low heritability. Thus, breeding drought-tolerant varieties is a fundamental way which can be used to increase rice yield in drought. To investigate the genetic basis of seedling tolerance to drought stress of rice (Oryza sativa L.), we performed QTL mapping on a big F2 population of 2600 participants from a cross between the japonica rice variety Huaidao 5 (HD5) and the indica rice variety 1892S through performing bulked segregant analysis and whole-genome sequencing (BSA-seq). HD5 showed greater tolerance to prolonged drought stress compared with1892Sat seedling stage. By analyzing a pair of opposite DNA pools made from 182 extremely-sensitive seedlings and 182 extremely-tolerant seedlings from the F2 population using the block regression mapping (BRM) method, we mapped a QTL on chromosome 1, of which the additive effect was estimated to explain 2.20% of the phenotypic variance. We named the QTLqSLDT1.1(q represents quantitative trait loci, SL represents seedling leaf, DT represents drought tolerance, 1.1representsthe first one found on chromosome 1), which must be a novel QTL, because no QTLs for rice seedling tolerance to drought stress have been mapped on chromosome 1 before. The information derived from the current research facilitates marker-assisted breeding of drought-resistant lines and positional cloning of the gene conferring drought tolerance in rice.
Keywords: Rice; Drought tolerance; QTL mapping; Bulked segregant analysis; Whole-genome sequencing